Caring, Repairing, and Reimagining: Experiences from the Rural World - Muñoz, Florencia; Greene Flaten, Ricardo.; Errázuriz, Tomás; Jacob Dazarola, Rubén. (Pontificia Universidad Católica de Chile, 2023)
In the era of the Anthropocene and amidst a severe environmental crisis, part of humanity has set out to imagine new ways of addressing global warming, hyperproduction of goods, and massive waste generation. Academia and public policies have placed their focus primarily on urban areas, neglecting the experiences that the rural world can offer us. Reversing this trend, this article focuses on a rural sector of the Central Valley of Chile to reveal how, through daily and ‘artisanal’ practices, it is possible to reimagine notions such as creativity, innovation, and adaptability, in the face of changing environments. Specifically, it recognizes the dynamic way in which the inhabitants of rural sectors comprehend objects and the environment; their particular way of living space and time within the local geography; and the role that their tools, technologies, practices, and knowledge play in the daily production of their homes.
Keywords: Crafts; Repair; Rurality; Cultura material; Herramientas